Flexible Learning by Design: Enhancing Faculty Digital Competence and Engagement Through the FLeD Project - Ana Afonso; Lina Morgado; Ingrid Noguera; Paloma Sepúlveda-Parrini; Davinia Hernandez-Leo; Shata N. Alkhasawneh; Maria João Spilker; Isabel Cristina Carvalho (Education Sciences, 2025)
Based on flipped learning, digital competence, and inclusive instructional design, this study employs a mixed-method approach (quantitative and qualitative) to evaluate the pilot and involves academics from six European universities. Teacher participants co-designed and implemented flexible learning scenarios using the FLeD tool, which integrates pedagogical patterns, scaffolding strategies, and playful features. Using a mixed-methods research approach, this study collected and analyzed data from 34 teachers and indirectly over 800 students. Results revealed enhanced student engagement, self-regulated learning, and pedagogical innovation. While educators reported increased awareness of inclusive teaching and benefited from collaborative design, challenges related to tool usability, time constraints, and the implementation of inclusivity also emerged. The findings support the effectiveness of structured digital tools in promoting pedagogical transformation in online, face-to-face, and hybrid learning. This study contributes to the discussion on the digitalization of higher education by illustrating how research-informed design can enable educators to develop engaging and flexible inclusive learning environments in line with the evolving needs of learners and the opportunities presented by technology.